Thickness dependent OER electrocatalysis of epitaxial LaFeO3 thin films. Issue 4 (5th January 2022) - Burton, Andricus R.; Paudel, Rajendra; Matthews, Bethany; Sassi, Michel; Spurgeon, Steven R.; Farnum, Byron H.; Comes, Ryan B.
Abstract : Epitaxial LaFeO3 exhibits thickness dependent OER electrocatalysis which balances catalysis at surface defect states with charge transport through the LaFeO3 film. Abstract : Transition metal oxides have long been an area of interest for water electrocatalysis through the oxygen evolution and oxygen reduction reactions. Iron oxides, such as LaFeO3, are particularly promising due to the favorable energy alignment of the valence and conduction bands comprised of Fe 3+ cations and the visible light band gap of such materials. In this work, we examine the role of band alignment on the electrocatalytic oxygen evolution reaction (OER) in the intrinsic semiconductor LaFeO3 by growing epitaxial films of varying thicknesses on Nb-doped SrTiO3 . Using cyclic voltammetry, we find that there is a strong thickness dependence on the efficiency of electrocatalysis for OER. These measurements are understood based on interfacial band alignment in the system as well as catalytically active surface defect states as confirmed by layer-resolved electron energy loss spectroscopy, electrochemical impedance spectroscopy, and Mott–Schottky measurements. Our results demonstrate the importance of band engineering for the rational design of thin film electrocatalysts for renewable energy sources.